Prognostic significance of initial computer tomography and neurological deficit in patients after cerebral stroke – an introductory report - Samojedna-Kobosz, Anna; Kwolek, Andrzej; Samojedny, Antoni (European Journal of Clinical and Experimental Medicine, 2009)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">We surveyed 50 patients (27 male, and 23 female patients), between 19 and 85 years of age, all of whom were diagnosed with brain ischemic stroke in the distribution area of middle cerebral artery (MCA). All patients underwent rehabilitation in rehabilitation ward. The time from incidence of stroke reached from I up to 10 years, and the length of ward stay was 3 up to 5 weeks. In this work we used results of examinations performed in the acute period of stroke in patients with symptoms of focal brain injury, ie. initial brain CT scan without contrast administration performed up to 12 hours after clinical symptoms onset and the initial clinical state evaluated after admission to neurology ward with SSS — data collected from medical documentation of 22 patients. To evaluate the clinical state and rehabilitation effects in rehabilitation ward we used: the Barthel Index, Rivermead Mobility Index and the Rankin Scale. Depending on the absence or presence of ischemic changes and their extent on brain CT scan, we divided patients into 3 groups: Group I — with the correct brain image, Group 2 — with early ischemic changes (EIC) < 1/3 of MCA territory, and Group 3 — with EIC > 1/3 of MCA territory. In all patients we observed clinical state improvement after rehabilitation. The efficiency of rehabilitation showed no relationship with the result of initial brain CT scan, but it correlated with the initial neurological deficit assessed with the SSS. The clinical state of patients at discharge from rehabilitation ward showed relationship with results of brain CT scans and the SSS result. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">1. The result of neuroimaging examination stays in connection with clinical state in patients after an episode of ischemic stroke, but it shows no importance in differentiating rehabilitation results in this ‘group of patients at the early stage. <p class="rtejustify" style="box-sizing: border-box; margin: 0px; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">2. The prognosis of final clinical state and rehabilitation effects in patients at the early stage of ischemic stroke must include the SSS results performed at the early stage